Heidegger's Hermeneutics as an Approach to Understanding Prophetic Hadith: A Nusantara Islamic Perspective - Sahjad M. Aksan; Muhammad Wardah; Muhammad Yaseen (Jurnal Lektur Keagamaan, 2026)
This study examines the application of Martin Heidegger's hermeneutical framework as an alternative method for understanding prophetic hadith through contextual, historical and existential perspectives. Employing a qualitative philosophical approach through systematic library research, the study analyzes selected hadiths from Sahih al-Bukhari, Sahih Muslim, and Musnad Ahmad using the concepts of Dasein, Being-in-the-world, and the hermeneutical circle. The findings demonstrate that Heideggerian hermeneutics situates hadith interpretation within the dynamic relationship between religious texts, the interpreter's existential horizon, and socio-historical context, thereby revealing dimensions of meaning that textual-formal approaches leave unaddressed. This research contributes to contemporary hadith studies by presenting a philosophical framework that bridges classical Islamic scholarly traditions and modern hermeneutical thought, offering Nusantara Islamic scholarship a methodologically grounded basis for developing contextual, moderate, and historically conscious interpretations of prophetic traditions. The implications extend to Islamic education and interdisciplinary inquiry, where hermeneutical analysis can strengthen engagement with contemporary religious and social challenges.